Beyond the Digital Divide: A Systematic Literature Review Exploring the Relationship between E-Learning Communication, Student Engagement, and Academic Performance - Diana Anggraini (Open Access Indonesia Journal of Social Sciences, 2025)
E-learning can support the creation of interpersonal communication for students, both students and lecturers. Even communication carried out in e-learning is considered to be one of the aspects that can affect student academic achievement. This study aims to explore themes in interpersonal communication and mediated communication in the context of e-learning. The method used in this study is Systematic Literature Review with the guidance of Preferred Reporting Items for Systematic reviews and Meta-Analyses/PRISMA 2020. Data was obtained from the Scopus research database by applying queries according to the research theme and 69 articles were obtained that will be further analyzed. The results of the study have succeeded in identifying 10 themes in interpersonal communication and 9 themes in mediated communication. Communication effectiveness, communication behavior, and social presence are things that need to be considered in interpersonal communication. As for mediated communication, it is necessary to consider the ease and comfort of communication, mediated communication behavior, and also the support of the online environment.